THE ROLE OF ULTRASONOGRAPHY IN THE DIAGNOSIS OF INFLAMMATORY AND DEGENERATIVE DISEASES OF THE HIP JOINT - Madumarova Z. Sh.; Xodjibekov M. Kh. (Web of Journals Publishing, 2024)
This article is devoted to the use of ultrasonography in the diagnosis of inflammatory and degenerative diseases of the hip joint. The article discusses the main indications for the use of ultrasound in the disease ostearthrosis (OA), the advantages and disadvantages of various methods of visualizing ultrasound used in OA of the thigh, performing an intra-articular injection of the hip joint under the supervision of an ultrasound. For a long time, a simple radiograph was considered the reference technique for osteoarthritis (OA). Recently, an innovative method of visualizing this disease is ultrasonography. The use of ultrasound identifies various anatomical structures in the smallest details and reveals small details of tissue changes.
Keywords: Osteoarthrosis, ultrasonography, scanning, hip joints.